2011
DOI: 10.1523/jneurosci.5129-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Fine Spatial Information Represented in a Population of Retinal Ganglion Cells

Abstract: Detailed measurement of ganglion cell receptive fields often reveals significant deviations from a smooth, Gaussian profile. We studied the effect of these irregularities on the representation of fine spatial information in the retina. We recorded from nearby clusters of ganglion cells, testing their ability to determine the location of small flashed spots, and we compared the results to the prediction of a Gaussian receptive field model derived from reverse correlation. Despite considerable receptive field ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
5
24
0
Order By: Relevance
“…At this point, the information carried by multiple retinal ganglion cells is, on average, redundant, so that the information per spike declines as we examine the responses of larger groups of neurons. Although the details of the experiments are different, the observation of coding redundancy at t lat is consistent with many previous results (9)(10)(11)(12)(13)(14)(15)(16)(17). However, the information that neural responses carry about position extends far into the past, t′ t − t lat , and more importantly…”
Section: Coding For the Position Of A Single Visual Objectsupporting
confidence: 87%
“…At this point, the information carried by multiple retinal ganglion cells is, on average, redundant, so that the information per spike declines as we examine the responses of larger groups of neurons. Although the details of the experiments are different, the observation of coding redundancy at t lat is consistent with many previous results (9)(10)(11)(12)(13)(14)(15)(16)(17). However, the information that neural responses carry about position extends far into the past, t′ t − t lat , and more importantly…”
Section: Coding For the Position Of A Single Visual Objectsupporting
confidence: 87%
“…More recently, electrical stimulation of individual cones in primate retina was shown to drive significant synaptic currents in parasol cells (Ala-Laurila et al, 2011). The present findings are also consistent with currents evoked in salamander RGCs by stimuli illuminating 1–2 cones (Soo et al, 2011), although again the number of cones feeding the RGCs was not reported.…”
Section: Discussionsupporting
confidence: 90%
“…RGC receptive fields exhibit large-scale structure that deviates from either circular or elliptical Gaussian profiles 12 . Heterogeneities on a finer scale have been measured as “hot-spots” within the receptive field that are unique for each RGC 1316 . Brown et al 15 measured fine-scale heterogeneity in the receptive fields of rabbit RGCs, but did not find a clear correspondence between the receptive field hot-spots and the dendritic patterns of individual RGCs.…”
Section: Introductionmentioning
confidence: 99%